ANALISIS PROFITABILITAS, RISK BASED CAPITAL (RBC) DAN PREMIUM GROWTH RATIO TERHADAP NILAI PERUSAHAAN: (Studi Keuangan pada Subsektor Asuransi yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2022-2024) - Annisa, Annisa Mardiana Ramdhani; Jhoansyah, Dicky; Nurmala, Resa (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
This study analyzes the effect of profitability, Risk Based Capital (RBC), and Premium Growth Ratio on firm value in insurance subsector companies listed on the Indonesia Stock Exchange for the period 2022-2024. Using a quantitative approach with associative methods. Data collection techniques using secondary data obtained from documentation and literature studies and IBM SPSS Version 30 software, as a tool for data analysis techniques. The population in this study is insurance subsector companies listed on the Indonesia Stock Exchange (BEI) for the period 2022-2024, with a total sample of 42 from the financial statements for 2022-2024 and using the perposive sampling method.  The results showed that profitability (ROE) had a significant effect on firm value, RBC also had a significant positive effect, while Premium Growth Ratio had no significant effect. Simultaneously, the three variables have a significant effect on the value of the Company.